Followership on Social Movements in Thai Civil Society - Kamphaengphet, Darin; Titilak, Saran (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
This article is a study of followers in the dimension of political social movements by documentary research base on critical theory and using the in-depth interview method of civil society. This article found that in any social movement consists of many groups of people which may together from an activist or an individual but they have a same concept based on the political Ideology of being a citizen, asking for the changes in practice through policy level. We can divided the followers’ characteristics into 6 types. 1) Courage to take personal responsibility 2) Courage to serve the leader 3) Courage to Challenge 4) Courage to make changes 5) Courage to make action in moral reasons (Moral Courage) 6) Courage to stand up without hierarchy. These characteristics are therefore based on a Thai style considered from the responsibility and actions is hegemony of follower. The major key success of leadership is to have productive or strongly supportive followers and being together till the end of the movements. This is we call the good followership outcomes